Conjunctival suture internal or external knotting in strabismus surgery: effect on healing and comfort - Gürez, Ceren; Hüseyinhan, Zahid; Gökyiğit, Birsen (The European Research Journal, 2022)
Objectives: To evaluate the effectiveness of the conjunctival suture tied internally and externally on patient comfort and suture dissolution in the postoperative period in patients who underwent symmetrical strabismus surgery. Methods: In 50 patients who underwent surgery in the Beyoğlu Eye Training and Research Hospital Strabismus Unit, the conjunctiva was closed by tying the conjunctival suture externally in the right eye and internally tying the left eye. Absorbable 8/0 polyglactin suture was used for conjunctival suturing in all patients. Pain, itching, tearing and, discomfort sensations of the patients were questioned and a slit-lamp examination for conjunctival inflammation and dissolution of the suture were evaluated on the postoperative 1st day, 1st week, 1st month, and 6th weeks. Results: Twenty-two patients were female and 28 were male. The mean age of the patients was 7.24 ± 4.83 (range: 4-17) years. When the pain, stinging and discomfort of the patients were questioned, 46% of the patients stated that they felt more comfortable in the left eye on the 1st and 10th days, while 48% of the patients stated that they were equal in both eyes. When we evaluated the melting of the suture and conjunctival redness, it was observed that the suture in the left eye was melted prematurely at a rate of 40% and, the conjunctival redness resolved early in the first month. There were equal pain and redness in both eyes at a rate of 54%. Conclusions: In strabismus surgery, the closure of the conjunctiva by tying the suture internally is thought to increase patient comfort in the postoperative period.